Effect of Transformational Leadership Style and Job Satisfaction on Employee Performance With Organizational Commitment As Interval Variables - Rina Irawati; Yuyuk Liana (Jurnal Ilmiah ESAI, 2013)
The purpose of this study was to examine the direct and indirect influence between transformational leadership style and job satisfaction on employee performance through organizational commitment. The samples were 84 employees of PT Dos Ni Roha by taking simple random sampling technique. Using path-analysis, the results proved that there is a direct influence between transformational leadership style and job satisfaction on job performance. Otherwise, there is no indirect effect between transformational leadership style and job satisfaction on job performance through organizational commitment. This is evidenced by the un-significant effect of transformational leadership style on job performance and organizational commitment. Results of this study are supported by previous research. By using path analysis, the model found a new path to eliminate the influence of transformational leadership style variable (X1). The dominant variables was indirect effect between job satisfaction on job performance through organizational commitment with the largest beta.Keywords: Transformational Leadership Style, Job Satisfaction, Organizational Commitment, Job Performance